Public policies for the development of a sustainable, forage-based cattle sector in Colombia, Argentina, and Costa Rica: A comparative analysis - Burkart, Stefan; Díaz, Manuel Francisco; Moreno Lerma, Leonardo (International Grassland Congress 2023, 2023)
Projected increases in global food demand highlight the importance of Latin America as one of the major future food suppliers, particularly regarding animal-source foods such as beef or milk. Despite the importance of the cattle sector for the region, its negative environmental impacts are numerous and the shift towards sustainability is perceived as slow and uncoordinated. This study aims to identify achievements and difficulties in the implementation of public policies for a sustainable cattle sector in Colombia, Argentina, and Costa Rica, for which policies focused on the use of silvo-pastoral systems and forage-based solutions are prioritized. Based on the review of scientific articles, government reports, and publications of international organizations, a comparative qualitative analysis was carried out, documenting the policy developments between 2010-2020. For the three countries, the findings highlight a large number of public policies focused on the implementation of silvo-pastoral systems, both at the local and national levels. At the same time, the efforts of the governments to include such strategies in the National Development Plans and stimulate legislative advances are evident. However, they also coincide in difficulties, such as the disconnection and lack of continuity between policies, unclear budgets for their financing, and little socialization within the communities. Another obstacle to the success of public policies is the way in which they are perceived by producers, who on many occasions refuse to make the transition from conventional to sustainable methods, considering that it implies the availability of economic resources, knowledge, and training that are difficult to access. The results also indicate that, despite the initiatives developed over the last ten years, problems such as deforestation and increasing greenhouse gas emissions persist in the three countries, although to different extents and at different levels. It is concluded that the policy efforts for the implementation of silvo-pastoral systems should be seen as initial steps in a longterm process towards achieving a sustainable cattle sector. Recommendations are provided that could help increase the success of these and new policies at different stages, from the identification of the problem to their evaluation, particularly given the difficulties of financing, disconnection, and participation of citizens and producers.